Penerapan Manajemen Mutu pada Proyek Pembangunan Rumah Susun Universitas Sains Al-Quran (UNSIQ) - Agustina, Hasnaa Anggia; Wicaksana, Joko Adi; Majjah, Ibnu; Ardiansyah, Raihan Prasetyawan (JUTEKS : Jurnal Teknik Sipil, 2024)
Competition in the construction services industry in Indonesia is currently tight, which has resulted in many construction companies that cannot compete going out of business. To survive, companies need to have a competitive advantage, one of which is through the quality of the products produced. Product quality is the key to gaining a sustainable competitive advantage. Quality management plays an important role in producing quality products. This research was conducted at Campus 2 of Al-Qur'an Science University (UNSIQ) Wonosobo, Central Java. The research used primary data through direct observation and secondary data obtained from project documents and relevant literature. The results showed that the construction project of the Al-Qur'an Science University Flats had reached the Quality Assurance stage but had not yet met the criteria of Total Quality Management (TQM). Nevertheless, the quality of the products produced has been guaranteed by the service provider in accordance with the existing contract. Higher quality management implementation can be pursued to achieve TQM and ensure more optimal product quality in the future.